Self-Determination Theory on Repurchase Intention of Green Product Mediating Customer Engagement: Study the Middle-Class Squeeze - Yuliatin Azizah; Mainatul Ilmi; Firna Yulia Puri; Alfina Dwi Susanti (ABM: International Journal of Administration, Business and Management, 2025)
This study investigates the role of customer engagement in shaping repurchase intentions for green products within a handicraft MSME community in Indonesia, using Self-Determination Theory (SDT) as a theoretical framework. SDT explains how the regulation of motivation from external to intrinsic drives individual engagement and purchasing behavior. The research context is middle-class squeeze, where consumers face increasing needs but limited purchasing power, creating challenges for sustainable consumption. A total of 354 respondents participated in the survey, and the data were analyzed using WarpPLS. The results of the structural model confirmed the validity and reliability of the measurement instrument. Identified and introjected motivations contributed significantly to engagement, while intrinsic motivation played a weaker role. Surprisingly, customer engagement did not significantly predict repurchase intentions, creating a paradoxical finding where high engagement does not necessarily translate into repeat purchases under economic constraints. These results highlight the complexity of sustainable consumer behavior during middle-class pressure and provide strategic implications for MSMEs, including the need for inclusive pricing, value-based communication, and gender-sensitive marketing approaches to strengthen repurchase intentions in the green product market.